A Molecular and Clinical Review of Stem Cell Therapy in Critical Limb Ischemia - Parikh, Punam P. (Stem Cells Int, 2017)
Peripheral artery disease (PAD) is one of the major vascular complications in individuals suffering from diabetes and in the elderly that can progress to critical limb ischemia (CLI), portending significant burden in terms of patient morbidity and mortality. Over the last two decades, stem cell therapy (SCT) has risen as an attractive alternative to traditional surgical and/or endovascular revascularization to treat this disorder. The primary benefit of SCT is to induce therapeutic neovascularization and promote collateral vessel formation to increase blood flow in the ischemic limb and soft tissue. Existing evidence provides a solid rationale for ongoing in-depth studies aimed at advancing current SCT that may change the way PAD/CLI patients are treated.